Analisis Diksi dan Gaya Bahasa pada Lirik Lagu Daerah Banten serta Pemanfaatannya dalam Pembelajaran Sastra di SMP - Purlilaiceu, Purlilaiceu; Saraswati, Sarasawati; Cucu Dawiyani Tanjung Sari (STKIP PGRI Bandar Lampung, 2025)
This study aims to analyze the use of diction and style of language in Bantenese folk song lyrics and explore their use in literature learning at the Junior High School (SMP) level. The specific objectives of this study are: (1) to describe the use of diction in Bantenese folk song lyrics, (2) to describe the use of style of language in Bantenese folk song lyrics, and (3) to describe the use of elements of diction and style of language in literature learning at SMP. The method used in this study is a qualitative descriptive method with text analysis techniques to identify and categorize the use of diction and style of language in Bantenese folk song lyrics. The results of the study indicate that Bantenese folk song lyrics are rich in distinctive diction that reflects local cultural values, as well as diverse styles of language such as personification, metaphor, and repetition. In addition, the results of the analysis indicate that these linguistic elements can be utilized effectively in literature learning at SMP, especially to increase students' appreciation of literary works based on local culture. This study recommends the integration of folk song lyrics into learning materials as an effort to preserve culture while strengthening students' language competence.